The Influence of Social Media, Brand Image and Location on the Decision to Stay at Imelda Hotel Kota Padang - Nanda, Nanda; Sa'dah, Lailatul (ADPEBI, 2024)
This study aims to determine the influence of social media, brand image and location on the decision to stay at imelda hotel in Padang city. The sampling technique uses an accidental sampling technique, using the Slovin formula so that a sample of 100 people is obtained. The F test was known that the value of fcal was 68,653 >from ftable 2.70 and the significance of f = 0.000 < 0.05, meaning that H4 was accepted and H0 was rejected. It can be said that Social Media, Brand Image, and Location simultaneously have a positive and significant effect on the decision to stay at Imelda Hotel. This means that social media variables, brand image and attraction location can explain the variables of the decision to stay at imelda hotels in Padang city, by 68.2%. The remaining 31.8% was explained by other variables that were not observed in this study.